Evidence-informed obstetric practice during normal birth in China: trends and influences in four hospitals - Liang Ji; Liang Hong; Smith Helen; Qian Xu; Garner Paul (BMC, 2006)
Abstract Background A variety of international organizations, professional groups and individuals are promoting evidence-informed obstetric care in China. We measured change in obstetric practice during vaginal delivery that could be attributed to the diffusion of evidence-based messages, and explored influences on practice change. Methods Sample surveys of women at postnatal discharge in three government hospitals in Shanghai and one in neighbouring Jiangsu province carried out in 1999, repeated in 2003, and compared. Main outcome measures were changes in obstetric practice and influences on provider behaviour. "Routine practice" was defined as more than 65% of vaginal births. Semi-structured interviews with doctors explored influences on practice. Results In 1999, episiotomy was routine at all four hospitals; pubic shaving, rectal examination (to monitor labour) and electronic fetal heart monitoring were routine at three hospitals; and enema on admission was common at one hospital. In 2003, episiotomy rates remained high at all hospitals, and actually significantly increased at one; pubic shaving was less common at one hospital; one hospital stopped rectal examination for monitoring labour, and the one hospital where enemas were common stopped this practice. Mobility during labour increased in three hospitals. Continuous support was variable between hospitals at baseline and showed no change with the 2003 survey. Provider behaviour was mainly influenced by international best practice standards promoted by hospital directors, and national legislation about clinical practice. Conclusion Obstetric practice became more evidence-informed in this selected group of hospitals in China. Change was not directly related to the promotion of evidence-based practice in the region. Hospital directors and national legislation seem to be particularly important influences on provider behaviour at the hospital level.